Electric, electronic and control engineering : proceedings of the 2015 International Conference on Electric, Electronic and Control Engineering (ICEECE 2015), Phuket Island, Thailand, 5-6 March 2015 - Shao, Fun; Shu, Wise; Tian, Tacy; International Conference on Electric, Electronic and Control Engineering (2015 : Phuket Island, Thailand). (Leiden : CRC Press, 2015)
Electric, Electronic and Control Engineering contains the contributions presented at the 2015 International Conference on Electric, Electronic and Control Engineering (ICEECE 2015, Phuket Island, Thailand, 5-6 March 2015). The book is divided into four main topics: - Electric and Electronic Engineering - Mechanic and Control Engineering - Information and Communication Technology - Environmental and Industrial Technology. Considerable attention is also paid to education science, chemical engineering, hydraulic engineering and civil engineering. The book will be useful to professionals and academics in electric, electronic, mechanic and control engineering, information and communication, and environmental and industrial technology.
Includes bibliographical references and index.
Keywords: Electrical engineering -- Congresses; Automatic control -- Congresses